The antitumor effect induced by an IL-2 ‘no-alpha’ mutein depends on changes in the CD8+ T lymphocyte/Treg cell balance - Carmenate, Tania; Montalvo, Galia; Lozada, Sum Lai; Rodriguez, Yaretnis; Ortiz, Yaquelin; Díaz, Claudia; Avellanet, Janet; Kim, Juhee; Surh, Charles D.; Graça, Luis; León, Kalet (Frontiers in Immunology, 2022)
High doses Interleukin-2 (IL-2) has been used for the treatment of melanoma and renal cell carcinoma, but this therapy has limited efficacy with a ~ 15% response rate. Remarkably, 7-9% of patients achieve complete or long-lasting responses. Many patients treated with IL-2 experienced expansion of regulatory T cells (Tregs), specifically the expansion of ICOS+ highly suppressive Tregs correlates with worse clinical outcomes. This partial efficacy together with the high toxicity associated with the therapy, have limited the use of IL-2 therapy. Taking into account the better understanding of IL-2 structure, signaling, and in vivo functions, some efforts to improve the cytokine properties are currently under study. In previous work, we described an IL-2 mutein with higher antitumor activity and less toxicity than wtIL-2. The mutein was in silico designed for losing the binding capacity to CD25 and for preferential stimulation of effector cells CD8+ and NK cells but not Tregs. The mutein induces a higher anti-metastatic effect than wtIL-2, but the extent of antitumor activity and the in vivo effect were still unexplored. In this work it is shown that the mutein induces strong antitumor effect on four primary tumor models, being effective even in those models where wtIL-2 doesn´t work. Furthermore, the mutein can change the in vivo balance between Tregs and T CD8+memory/activated cells towards immune activation, both in healthy and tumor-bearing mice. This change reaches the tumor microenvironment and seems to be the major explanation for the mutein efficacy in vivo.